ПІВДЕНЬ УКРАЇНИ У РЕВОЛЮЦІЙНИХ ПОДІЯХ 1917 ñ ПОЧАТКУ 1918 рр. (ДЖЕРЕЛОЗНАВЧИЙ АСПЕКТ) (Zaporizhzhia Historical Review, 2021)
The representativness of the source base as for the educating the main problems of the social-economic and social - political development of the south of Ukraine in the period of the Ukrainian Central Rada is analysed